Can the induction of incidental positive emotions lead to different performances in sequential decision-making?. Issue 7 (2nd October 2020) - Mailliez, Mélody; Bollon, Thierry; Graton, Aurélien; Hot, Pascal
ABSTRACT: A growing body of evidence suggests that emotional states under which individuals perform decision-making tasks modulate performance. Studies have mainly reported that negative emotions can differentially increase or decrease performance by modulating feedback processing. In contrast, differential influences of specific emotions inside positive valence have been poorly investigated. The objective of the present work was to assess specific effect of different types of positive emotions on decision-making and to investigate whether this effect also depends on feedback processing. In our study, after being induced to feel either hope or happiness, participants undertook a risky sequential decision-making task in which feedback was required to obtain a good performance. We found that the more positive was the feedback received, the more happiness led participants to make risky decisions. This tendency was not observed among participants in the hopeful or in the control condition. Our results contribute to the literature showing that the effects of emotions on sequential decision-making performance can be explained by feedback processing and are not solely due to the valence of the emotional state. They also suggest that further research is required to determine which potential specific dimension is involved in the effects of positive emotions on sequential decision-making.